Long‐Term Outcomes of Patients With Mediastinal Radiation–Associated Severe Aortic Stenosis and Subsequent Surgical Aortic Valve Replacement: A Matched Cohort Study. Issue 5 (5th May 2017) - Donnellan, Eoin; Masri, Ahmad; Johnston, Douglas R.; Pettersson, Gosta B.; Rodriguez, L. Leonardo; Popovic, Zoran B.; Roselli, Eric E.; Smedira, Nicholas G.; Svensson, Lars G.; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: Cardiac disease after mediastinal radiotherapy for thoracic malignancy (chest radiotherapy [XRT]) often manifests as progressive aortic stenosis. In patients with XRT‐induced severe aortic stenosis undergoing surgical aortic valve replacement (SAVR), we sought to: (1) study long‐term survival and compare these patients with a matched cohort undergoing SAVR during the same time frame; and (2) identify potential predictors of long‐term mortality. Methods and Results: We studied patients with symptomatic severe aortic stenosis undergoing SAVR at our institution, of which there were 172 mediastinal XRT patients (63±13 years, 62% women) matched in a 1:1 fashion (based on age, sex, time of surgery, and aortic valve area) with 172 non‐XRT patients (comparison group). Baseline clinical and postoperative data were obtained. Society of Thoracic Surgeons score was calculated and mortality was recorded. In the XRT group, the median Society of Thoracic Surgeons score was 4% (interquartile range 2–13), while mean left ventricular ejection fraction, left ventricular stroke volume index, and mean aortic valve gradient were 54±11%, 38±14 mL/m 2, and 39±11 mm Hg, respectively. In the entire cohort, 27% and 34% of patients underwent concomitant coronary artery bypass grafting and aortic surgery at the time of SAVR, respectively. Thirty‐day/in‐hospital deaths occurred in 4 (2%) patients in the XRT group and 0 patients in the comparison group. At 6±3 years of follow‐up, on matched group analysis, there were 95 (28%) deaths (83 [48%] in the XRT group versus 12 [7%] in the comparison group (log‐rank 89, P <0.001). On multivariable Cox survival analysis, in the whole cohort, higher Society of Thoracic Surgeons score (hazard ratio, 1.14; 95% CI, 1.03–1.26) and mediastinal XRT (hazard ratio, 8.12; 95% CI, 4.26–15.64) were associated with increased longer‐term mortality (both P <0.01). Conclusions: In patients with severe aortic stenosis undergoing SAVR, patients with prior mediastinal XRT have significantly worse longer‐term survival versus a matched cohort.